Analysis of the Impact of Recruitment and Selection as A Strategic Human Resource Management Tool on Organizational Performance in Zambia - Mwambela, Able; Bwacha, Isaac Kabunda (Indonesian Journal of Community Services, 2025)
This study aims to examine how the strategic implementation of recruitment and selection impacts organizational performance. 169 managers from profit-making organizations in Zambia participated in the research, and a quantitative approach was used to gather data.  The questionnaire had three parts: the first part gathered demographic data, the second part collected information about strategic human resource management (HRM) practices, and the third part obtained data on organizational performance. The study focused on a stratified random sample of 169 managers from various organizations. The results indicated that incentives and rewards were significant for achieving excellence, followed by recruitment and selection, and were followed by formal performance appraisal, which had a minor impact on career development. There is a notable correlation between strategic HRM components and organizational performance, including the revenue growth rate, return on equity, return on assets, and overall profitability (p < 0.01). The findings indicate that organizations should strategically align their activities to enhance performance, particularly recruitment, which has a direct impact on the organization's output. Furthermore, the research concludes that strategic human resource management (HRM) practices play a pivotal role in propelling organizational performance and should be harmonized with overarching business strategies and operations.